FORMATION OF COMMUNICATIVE COMPETENCE IN THE PROCESS OF FOREIGN LANGUAGE LEARNING PROFESSIONALLY - Havrylyuk, O.O. (Pedagogy of Higher and Secondary Education, 2009)
The article devotes to the problem of forming communicative competence of the students in the process of learnin foreign languages professionally oriented.